PHYTOCHEMICAL SCREENING, TOTAL ANTIOXIDANT ACTIVITY AND TOXICITY TEST ON METHANOL EXTRACT OF ANDROGRAPHIS PANICULATA LEAF - Thalia Gabriella Siriwa; Frans Ferdinal (Jurnal Kesehatan Tambusai, 2023)
Antioxidants are compounds that can inhibit the oxidation of a molecule and neutralize radicals that have a negative impact on cells. In addition, antioxidants can also inhibit the activity of reactive oxygen species (ROS) by regulating the superoxide dismutase enzyme. When the level of ROS is greater than that of antioxidants, an imbalance state called oxidative stress can occur. In this case, antioxidants play an important role in preventing ROS activity. Sambiloto or, "King of Bitter," is one of the herbal plants that contain antioxidants and often used as traditional medicine. Phytochemicals are chemical compounds produced by herbal plants, which can act as anti-inflammatory, antidiabetic, antimicrobial, antiparasitic, antidepressant, anti-cancer, antioxidant, and wound healing. This study aims to increase knowledge about the antioxidant ability and toxicity of Sambiloto leaf. This study used an in-vitro experimental and bioassay study consisting of qualitative phytochemical tests (Harborne), total antioxidant capacity with DPPH (Blois), total phenolic content (Singleton and Rossi), total alkaloid content (Trivedi et al) and toxicity test with BSLT. The results showed that the phytochemical test of Sambiloto leaf extract contained alkaloids, cardio glycosides, flavonoids, glycosides, phenolics, saponins, quinones, steroids, terpenoids, tannins, coumarins, and betacyanins; total antioxidant capacity (IC50=104.22 µg/mL); mean total phenolic content (392.19 µg/mL); mean total alkaloid content (9.47 µg/mL); toxicity test (LC50=107.54 g/mL). It can be concluded that Sambiloto leaf extract has the potential to be antioxidant and cytotoxic.